Analysis of Soil Microbial Community Structure and Function in Morchella esculenta Habitats in Jilin Province - Qi Yan; Peng Wang; Zhushan Liu; Ya Yu; Xiao Tan; Xiao Huang; Jiawei Wen; Weidong Zhang (Agronomy)
Morel mushrooms (Morchella spp.), a globally distributed edible and medicinal fungus, possess significant economic and nutritional values. This study investigated rhizosphere soil samples collected from wild Morchella esculenta in three regions of Jilin Province. Metagenome sequencing technology was employed to analyze the structure and function of the rhizosphere microbial communities. The results indicated significant differences in microbial community composition among the samples, with the bacterial community being dominant, followed by the archaeal community. Pseudomonadota and Nitrospirae emerged as the dominant phyla, while Bradyrhizobium and Nitrospira were the co-dominant genera. A correlation analysis of environmental factors revealed that the genera Luteibacter, Streptomyces, Micromonospora, Nocardia, Actinomadura, and Paenibacillus were positively correlated with soil total nitrogen, total phosphorus, and organic matter content. In contrast, Candidatus Nitrosocosmicus showed a significant positive correlation with rapidly available nutrients. The functional annotation analysis of soil microorganisms, based on the KEGG database, revealed that within level A (highest tier), metabolic activities were the most prominent. In contrast, at level B (secondary tier), global and overview maps, carbohydrate metabolism, and amino acid metabolism were dominant. Among the top 10 pathway-level annotations, metabolic pathways, the biosynthesis of secondary metabolites, and microbial metabolism in diverse environments were significant. Environmental factors and KEGG gene network maps indicated that the available potassium, available phosphorus, and pH were closely related to level A genes, which exhibited a higher abundance of metabolism genes. This study was dedicated to deepening the understanding of the structure and function of the rhizosphere microbial community of Morchella esculenta, and providing new perspectives and insights for habitat investigations, the development of biomimetic cultivation techniques, and the domestication of wild strains to Morchella esculenta in Jilin Province.